Implemetasi Peraturan Presiden Nomor 87 Tahun 2016 tentang Satuan Sapu Bersih Pungutan Liar pada Lingkup Sekolah (Studi Kasus Di Kecamatan Abuki Kabupaten Konawe) - Dendi Aditia; Aris Nur Qadar Ar. Razak (QAIMUDDIN: Journal of Constitutional Law Review, 2021)
The purpose of the study to (1) learn what factors affect the free ride at school (2) know the effects of high school illegal attacks, and (3) know the implementation of the 2016 presidential rule number 87 of 2016 reference to the ilk cleaning unit of state 1 Abuki high school. The method of data collection in this study is divided into two, namely, literature study methods and field research methods. The mthod of data analysis used is qualitative analysis composed of the stage of data reduction, data presentation, and deducation drawing. Research indicates that (1) factors of the emergence of illegal practices in the school range of individual perpetrators, opportunities, regulation and regulations are unclear, surveillance, punishment, and low society participation in the fight against illegal school practices. (2) The repercussions of the practice of illegal schooling are to impede the educational process of learners’ education, to the detriment of learners, and to undermine the educational order/system at school. (3) The implementation/implementation of Presidential Regulation No. 87 of 2016 concerning the Illegal Charges Sweeping Task Force (Satgas Saber Pungli) in schools, especially at SMAN 1 Abuki has not been carried out optimally because there has been no socialization carried out by the Saber Pungli Unit Kab. Konawe at SMAN 1 Abuki and its effect is the donation that is enforced at SMAN 1 Abuki is referred to in the practice of illegal levies in accordance with what was said by Mastri Susilo, Chair of the Southeast Sulawesi Ombutsman who stated about the types of illegal levies that often occur in schools, namely payment of money. committee, payment for grade corrections, payment for writing semester grade reports, payment for writing diplomas, class fees, tuition fees, scout fees, sports clothes fees, study tour fees, and fees for building school prayer rooms. and the community also has a big role to play in assisting the saber extortion task force in combating illegal levies.